Network Time Where it Counts. Temporality and Critical Approaches to Infrastructure. (28th July 2017) - Schofield, Tom; Arrigoni, Gabriella
Abstract: The default position towards temporality in designing for the web is to treat it as unfortunate constraint that negatively affects user experience. In contrast we look to the complex temporal interactions of networked technologies as a site of theoretical and aesthetic interest with the power to engage users in speculative and critical attitudes towards technical infrastructure. We argue that by valorising the temporality of networks and considering new forms of representation we open a range of creative possibilities with the potential to engage users in fundamental questions about technological infrastructure: who owns it, where it is and how it intra-acts. We provide examples of two artworks that treat with the subject of network time and discuss a basic guiding taxonomy to inform future work in design.